Two differentially structured collagen scaffolds for potential urinary bladder augmentation: proof of concept study in a Göttingen minipig model. Issue 1 (December 2017) - Leonhäuser, Dorothea; Stollenwerk, Katja; Seifarth, Volker; Zraik, Isabella; Vogt, Michael; Srinivasan, Pramod; Tolba, Rene; Grosse, Joachim
Abstract Background The repair of urinary bladder tissue is a necessity for tissue loss due to cancer, trauma, or congenital abnormalities. Use of intestinal tissue is still the gold standard in the urological clinic, which leads to new problems and dysfunctions like mucus production, stone formation, and finally malignancies. Therefore, the use of artificial, biologically derived materials is a promising step towards the augmentation of this specialised tissue. The aim of this study was to investigate potential bladder wall repair by two collagen scaffold prototypes, OptiMaix 2D and 3D, naïve and seeded with autologous vesical cells, as potential bladder wall substitute material in a large animal model. Methods Six Göttingen minipigs underwent cystoplastic surgery for tissue biopsy and cell isolation followed by implantation of unseeded scaffolds. Six weeks after the first operation, scaffolds seeded with the tissue cultured autologous urothelial and detrusor smooth muscle cells were implanted into the bladder together with additional unseeded scaffolds for comparison. Cystography and bladder ultrasound were performed to demonstrate structural integrity and as leakage test of the implantation sites. Eighteen, 22, and 32 weeks after the first operation, two minipigs respectively were sacrificed and the urinary tract was examined via different (immunohistochemical) staining procedures and the usage of two-photon laser scanning microscopy. Results Both collagen scaffold prototypes in vivo had good ingrowth capacity into the bladder wall including a quick lining with urothelial cells. The ingrowth of detrusor muscle tissue, along with the degradation of the scaffolds, could also be observed throughout the study period. Conclusions We could show that the investigated collagen scaffolds OptiMaix 2D and 3D are a potential material for bladder wall substitution. The material has good biocompatible properties, shows a good cell growth of autologous cells in vitro, and a good integration into the present bladder tissue in vivo.